2009
DOI: 10.5539/ijef.v1n1p40
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Earnings and Stock Returns: Empirical Evidence from the Greek Capital Market

Abstract: The relationship between earnings figures and stock returns has been a topic of international research since decades. The purpose of this paper is to investigate the above relationship in the context of the Greek capital market. Previous studies resulted in controversial results regarding the usefulness of models which were using earnings levels or earnings changes as the explanatory variable. In an introductory context, this study examines the earnings-return relation applying four models, proposed by Kothari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
(28 reference statements)
4
9
0
2
Order By: Relevance
“…By using a sample of listed Polish firms, Jermakowicz and Gornik-Tomaszewski (1998) found that earnings per share were relevant and significantly influence market share price. Similar results reported in Greek capital market by Dimitropolous (2005). On the other hand, Halonen, Pavlovic, and Persson (2013) in Sweden showed an increase in the value relevance of book value per share as compared to earnings per share.…”
Section: Review Of Literaturesupporting
confidence: 89%
“…By using a sample of listed Polish firms, Jermakowicz and Gornik-Tomaszewski (1998) found that earnings per share were relevant and significantly influence market share price. Similar results reported in Greek capital market by Dimitropolous (2005). On the other hand, Halonen, Pavlovic, and Persson (2013) in Sweden showed an increase in the value relevance of book value per share as compared to earnings per share.…”
Section: Review Of Literaturesupporting
confidence: 89%
“…Moreover, investors should aim towards greater value of mentioned ratios due to them being a proxy for performance measurement of firms and efficiency of their management. That is why investors should aim greater values of EPS, ROA and ROE (evidence was found as well as in Dimitropoulos and Asteriou (2009) and Palepu and Healy (2010)). Finally, the positive relationship between the Dividend per Share (DPS) ratio and expected returns has been found very early in the literature in work of Fama and Schwert (1977) and Campbell (1987); and has been continuously confirmed over the years as well in Fama and French (1988), Campbell and Shiller (1988), Kothari and Shanken (1997) or Lewellen (2004).…”
Section: Data Description and Rationale For Used Factorsmentioning
confidence: 85%
“…Informasi laba akan diperoleh investor melalui laporan keuangan perusahaan. Angka laba diperkirakan dapat memfasilitasi analis dan investor untuk meramalkan aliran kas di masa depan dan bertransaksi dengan risiko investasi yang Calyptra: Jurnal Ilmiah Mahasiswa Universitas Surabaya Vol.5 No.2 (2016) relatif (Dimitropoulos, 2009). Menurut Syafrudin (2004), investor merespon secara berbeda terhadap informasi laba akuntansi sesuai dengan kredibilitas atau kualitas informasi laba akuntansi tersebut.…”
Section: Pendahuluanunclassified